Using a delayed coincidence counting system to determine ²²³Ra, ²²⁴Ra in seawater sample - Vo Thi, Mong Tham; Phan, Son Hai; Nguyen, Van Phuc; Nguyen, Minh Dao; Phan, Quang Trung; Le, Xuan Thang; Nguyen Thi, Huong Lan (Nuclear Science and Technology, 2018)
A Radium Delayed Coincidence Counter (RaDeCC) includes 3 channels (223Ra channel, 224Ra channel, and total channel). It has been newly designed and assembled at Nuclear Research Institute. To determine 223Ra and 224Ra in seawater samples, the system efficiency at all 3 channels were investigated and calibrated. The research results showed that the RaDeCC operates stably and reliably with high efficiency of 26%. In this project, a procedure for measuring short half-life radium isotopes was established with a low detection limit (LOD (223Ra) = 0.002 Bq; LOD (224Ra) = 0.01 Bq), good reproducibility, and high precision. The technique is suitable for qualitative analysis of 223Ra, 224Ra in seawater samples at low concentration. The 11 coastal water samples were collected in a coastal of Ninh Thuan province. The analytical data of short-lived radium isotopes concentration in seawater at Ninh Thuan coastal area are 11.2 × 10-3 ÷ 45.5 × 10-3 mBq/L for 223Ra, and 34.7 × 10-2 ÷ 21.9 × 10-1 mBq/L for 224Ra.